KEMAMPUAN MANAJERIAL KEPALA SEKOLAH DAN KOMITE SEKOLAH PENGARUHNYA TERHADAP BUDAYA ORGANISASI DAN EFEKTIFITAS PENYELENGGARAAN SEKOLAH - Masrukhin, Masrukhin (Program Studi Pendidikan Agama Islam, 2018)
This study aims to find, describe, predict and verify the theory. Type of survey research with quantitative approach. Sampling technique was done gradually with Cluster Sampling or Sampling Area at High School as many as 100 schools from 105 schools. Data collection using questionnaire. This research consists of two variables, namely exogenous latent variable in this research is the Managerial ability of headmaster (x1) and School Committee (x2). Endogenous latent variables in School Organization Culture (η1) and School Effectiveness (η2). Data analysis techniques used Structural Equation Modeling (SEM). Based on the results of descriptive statistical analysis both exogenous and endogenous latent variables included in good category. Theoretical model expressed fit. The magnitude of the effect of each exogenous variable on the endogenous variable and the contribution of the construct indicator are: (1) School effectiveness is not determined directly by the Managerial ability of headmaster, (2) The School Organization Culture is determined by the Managerial ability of headmaster, (3) School Effectiveness is determined not (4) School effectiveness is not defined by the School Committee, (5) School Organization Culture is not determined by the School Committee, (6) School Effectiveness is not determined directly by the School Committee through School Organization Culture, (7) School effectiveness is determined directly by the School Organization Culture. The contribution of each indicator to the construct is: (1) Managerial ability of headmaster variable is the M3 (Technical Skill) dimension, with a value of R² of 0.76 or 76%., (2) School Committee variable is the K3 dimension (Advisory Agency ), with a R2 value of 0.92 or 92%, (3) School Organization Cultural variable is the dimension of B4 (Philosphy), with an estimated value of 0.67, (4) School Effectiveness variable is the dimension E4 (Standards of Teachers) with an estimated value of 0.99.